2020
DOI: 10.2147/dddt.s203048
|View full text |Cite
|
Sign up to set email alerts
|

<p>NVP-BSK805, an Inhibitor of JAK2 Kinase, Significantly Enhances the Radiosensitivity of Esophageal Squamous Cell Carcinoma in vitro and in vivo</p>

Abstract: Purpose: Radiotherapy is one major curative treatment modality for esophageal squamous cell carcinoma (ESCC) patients. This study aimed to find out small-molecular kinase inhibitors, which can significantly enhance the radiosensitivity of ESCC in vitro and in vivo. Materials and Methods: Ninety-three kinase inhibitors were tested for their radiosensitizing effect in ESCC cells through high-content screening. The radiosensitizing effect of kinase inhibitors was investigated in vitro by detection of DNA double-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Radioresistance is the focus and difficulty in cancer radiobiology research, which is also a clinically urgent issue ( Wang et al, 2019 ; Yu et al, 2020 ; Sun et al, 2021 ; Liu et al, 2022 ). Genes are an intrinsic determinant of tumor radioresistance, and studies have shown that multiple genes can affect the radioresistance of esophageal cancer ( Huang et al, 2019 ; Wang et al, 2019 ; Hua et al, 2020 ; Yu et al, 2020 ; Han et al, 2021 ; Sun et al, 2021 ; Liu et al, 2022 ). Practice has shown that it is common in clinical practice that even patients with esophageal cancer of the same stage and the same pathological type have great differences in the effect of radiotherapy after receiving the same radiotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioresistance is the focus and difficulty in cancer radiobiology research, which is also a clinically urgent issue ( Wang et al, 2019 ; Yu et al, 2020 ; Sun et al, 2021 ; Liu et al, 2022 ). Genes are an intrinsic determinant of tumor radioresistance, and studies have shown that multiple genes can affect the radioresistance of esophageal cancer ( Huang et al, 2019 ; Wang et al, 2019 ; Hua et al, 2020 ; Yu et al, 2020 ; Han et al, 2021 ; Sun et al, 2021 ; Liu et al, 2022 ). Practice has shown that it is common in clinical practice that even patients with esophageal cancer of the same stage and the same pathological type have great differences in the effect of radiotherapy after receiving the same radiotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Practice has shown that it is common in clinical practice that even patients with esophageal cancer of the same stage and the same pathological type have great differences in the effect of radiotherapy after receiving the same radiotherapy regimen. The fundamental reason is the genetic differences between different individuals ( Huang et al, 2019 ; Wang et al, 2019 ; Hua et al, 2020 ; Yu et al, 2020 ; Han et al, 2021 ; Sun et al, 2021 ; Liu et al, 2022 ). If the decisive genes of radioresistance can be screened out, it is of great significance for the study of radiosensitization, targeted therapy, and prediction of radiotherapy effect to guide individualized therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated an attractive prospect of NVP-BSK805 in HNSCC. 355 CDK4/6 inhibitors The effect of CDK4/6 inhibitors is a hotpot in HNSCC. [356][357][358][359][360] Abemaciclib is the first CDK4/6 inhibitor that has been widely investigated.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%